Enhancing the role of informal sector in food security and poverty reduction in malawi-policy implications and recommendations - Aston Oliver Mulwafu (Department of Agricultural Extension, College of Horticulture, 2012)
Malawi is a land-locked country located in the Southern Africa along the Great Rift Valley. The country has a population of approximately 14 million people, of which 51 per cent are women. Agriculture is the mainstay of the economy, providing livelihood to 80 per cent of the population and generating 35 to 45 per cent of GDP.